On the Study of Fauna (Macroinvertebrates, Fish, Amphibians, Reptiles, Birds and Mammals) of the Lower Course of Shokhdara River Valley in Pamir, Mountain Bodakhshan, Tajikistan - Afanasyev, S. A.; Marushchak, O. Yu.; Lietytska, O. M.; Abdulnazarov, A.; Golub, O. O.; Domashevsky, S. V.; Gavris, G. G. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2024)
This paper contains information on the records of bottom macroinvertebrates, fish, amphibians, reptiles, birds and mammals collected during a field expedition to the valley of the Shokhdara River (in the vicinities of town of Khorog city) near its mouth and confluence with Panj River in autumn 2019 – spring 2020. According to the results of the study, 3 fish species (Actinopterigii) were found inhabiting Shokhdara River with 1 additional species being confirmed by locals. The taxonomic composition of the registered fish species is as follows: Cyprinidae – 2, Nemacheilidae – 1. 5 species of reptiles (Squamata: Colubridae – 2, Viperidae – 1, Agamidae – 1, Gekkonidae - 1), and 1 species of amphibians (Anura: Bufonidae – 1) were registered within the investigated area. 24 taxonomic groups of water macroinvertebrates were spotted (89,7% - Insecta): Simuliidae - 35,8%, Ephemeroptera – 18,7%, Chironomidae – 18%, Trichoptera – 10,5%, Oligochaeta – 6,5%, Plecoptera – 2,8%, Diptera – 2,5%, Gastropoda – 2,5%. Nematoda, Turbilaria, Ostracoda, Copepoda, Сyclops, Sphaerium, Araneida, Acarina, Odonata, Heteroptera, Colleoptera, Neuroptera, Lepidoptera and Megaloptera in total counted as only 2,7% of all registered macroinvertebrates. A total of 99 bird species (48% of the avifauna of the studied region) were registered during autumn/spring research. Among Mammalia class such valuable and rare internationally protected species as Asian otter, snow leopard and Himalayan brown bear were confirmed to inhabit the areas adjacent to the studies river valley.